Students’ perceptions on difficult reading question types - Hermida, Rita (Accentia: Journal of English Language and Education, 2023)
As one of the language skills, reading also has two types of testing, namely subjective and objective testing. Each type of test has several forms. Although teachers must have their own purposes in choosing what type of test should be given to the students, some types of tests look more difficult than others. This is what this study focused on. The aim of this study is to look deeper into what and why some types of tests seem difficult to students, especially to Darul Ihsan students, which consist of 28 students. The result of this study shows that prediction, conclusion, details, and purposes are the most difficult question types. Meanwhile, the main idea, reference, and inference are quite difficult. In addition, the title, synonym, and antonym are not really difficult for them. The reasons behind this were that predictions, conclusions, details, and purposes need much critical thinking and background knowledge. This was what the students faced and surely should be a vital consideration in the teaching and learning process.